Glucagon-like peptide-1 receptor agonists in neurodegenerative diseases: Promises and challenges - Zhi Dong Zhou; Lingxiao Yi; Karolina Popławska-Domaszewicz; Kallol Ray Chaudhuri; Joseph Jankovic; Eng King Tan (Pharmacological Research)
Glucagon-like peptide-1 (GLP-1) receptor agonists (GRA) belong to a class of compounds that reduce blood glucose and energy intake by simulating actions of endogenous incretin hormone GLP-1 after it is released by the gut following food consumption. They are used to treat type 2 diabetes mellitus (T2DM) and obesity and have systemic effects on various organs, including the brain, liver, pancreas, heart, and the gut. Patients with T2DM have a higher risk of developing neurodegenerative diseases (NDs), including Alzheimer’s disease (AD), Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS) and Huntington’s disease (HD), accompanied by more severe motor deficits and faster disease progression, suggesting dysregulation of insulin signaling in these diseases. Experimental studies have shown that GRA have protective effects to modulate neuroinflammation, oxidative stress, mitochondrial and autophagic functions, and protein misfolding. Hence the compounds have generated enormous interest as novel therapeutic agents against NDs. To date, clinical trials have shown that three GRA, exenatide, liraglutide and lixisenatide can improve motor deficits as an add-on therapy in PD patients and liraglutide can improve cognitive function in AD patients. The neuroprotective effects of these and other GRA, such as PT320 (a sustained-released exenatide) and semaglutide, are still under investigation. The dual GLP-1/gastric inhibitory polypeptide (GIP) receptor agonists have been demonstrated to have beneficial effects in AD and PD mice models. Overall, GRA are highly promising novel drugs, but future clinical studies should identify which subsets of patients should be targeted as potential candidates for their symptomatic and/or neuroprotective benefits, investigate whether combinations with other classes of drugs can further augment their efficacy, and evaluate their long-term disease-modifying and adverse effects.